A Pilot Study to Examine the Effect of Passive Straight Leg Raise Performed During Cardiopulmonary Resuscitation on Cerebral Perfusion Measured by Noninvasive Cerebral Oximetry. (27th March 2023) - Lorensini, Scott; Prakash, Shivesh; McNeill, David; Spencer, Neil; Bihari, Shailesh
Abstract : OBJECTIVES: Passive leg raise (PLR) during cardiopulmonary resuscitation (CPR) is simple and noninvasive maneuver, which can potentially improve patient-related outcomes. Initial CPR guidelines have previously advocated "elevation of the lower extremities to augment artificial circulation during CPR." There is lack of supporting evidence for this recommendation. DESIGN: This was a double cross-over physiologic efficacy randomized study. SETTING AND PATIENTS: Study in 10 subjects with in-hospital cardiac arrest for whom CPR was undertaken. INTERVENTION: Subjects were randomized to receive two cycles of CPR with PLR followed by two cycles of CPR without PLR (Group I) or vice-versa (Group II). Subjects had their foreheads (right and left) fitted with near infrared spectroscopy (NIRS) electrodes (O3 System-Masimo, Masimo corporation Forty Parker, Irvine CA) while undergoing CPR during the study. NIRS readings, a measure of mixed venous, arterial, and capillary blood oxygen saturation, act as a surrogate measure of cerebral blood perfusion during CPR. MEASUREMENT AND MAIN RESULTS: PLR was randomly used "first" in five of them, whereas it was used "second" in the remaining five subjects. In subjects in whom PLR was performed during first two cycles (Group I), NIRS values were initially significantly greater. The performance of PLR during CPR in Group II attenuated the decline in NIRS readings during CPR. CONCLUSIONS: PLR during CPR is feasible and leads to augmentation of cerebral blood flow. Furthermore, the expected decline in cerebral blood flow over time during CPR may be attenuated by this maneuver. The clinical significance of these findings will require further investigations.